2019
DOI: 10.1136/bmjinnov-2017-000257
|View full text |Cite
|
Sign up to set email alerts
|

Development of an online secondary prevention programme for stroke survivors: Prevent 2nd Stroke

Abstract: BackgroundStroke events often result in long-term negative health outcomes. People who experience a first stroke event are 30%–40% more likely to experience a second stroke event within 5 years. An online secondary prevention programme for stroke survivors may help stroke survivors improve their health risk behaviours and lower their risk of a second stroke.ObjectivesThis paper describes the development and early iteration testing of the usability and acceptability of an online secondary prevention programme f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Recent studies suggested that an online secondary stroke prevention program is an effective way to modify behaviors and lifestyles. 50,51 The promotion of such strategies to improve secondary prevention of stroke is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that an online secondary stroke prevention program is an effective way to modify behaviors and lifestyles. 50,51 The promotion of such strategies to improve secondary prevention of stroke is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…A generic framework was used in less than half (3/8, 38%) of these studies; Pitt et al [ 42 , 43 ] reported that their intervention had been developed according to a guide for complex intervention development that was not specific to digital health, while Rietdijk et al [ 44 ] referred to a generic framework for feasibility to inform study design. Almost twice as many (5/8, 63%) referred to a framework specific to the development of digital interventions, including web-based education [ 45 ], web-based programs [ 46 ], and user-centered design [ 47 - 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In each study, the nature of ABI and the psychosocial condition under treatment was almost always (56/60, 93%) complicated because it was “not fully characterized or understood” [ 17 ], yet not quite complex because participants were usually recruited in the chronic stages of injury to control for spontaneous recovery. In the remaining 7% (4/60) of studies, the condition shifted into the “unpredictable or high risk” definition of complex when investigators documented that participants experienced multiple neurological events [ 46 , 62 , 63 ] and responded unexpectedly to intervention during the chronic stage of injury [ 62 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The P2S program was developed using behaviour change theory and co-design principles with stroke survivors, and was pilot tested prior to this trial. The development and testing of the intervention have been described in detail elsewhere [ 24 , 25 ]. Briefly, the P2S program is a modularised, tailored program providing evidence-based techniques and information in 6 core modules: (1) blood pressure, (2) smoking, (3) alcohol consumption, (4) physical activity, (5) nutrition, and (6) feelings and mood, as well as a ‘my progress’ section.…”
Section: Methodsmentioning
confidence: 99%
“…The primary aim was to evaluate the effectiveness of an online health behaviour change intervention—Prevent 2nd Stroke (P2S)—at improving HRQoL amongst stroke survivors at 6 months of follow-up. The development of the P2S program [ 24 ] and acceptability and feasibility piloting [ 25 ] of the program have been reported elsewhere. Secondary aims were to examine the effect of the online P2S program on 4 health behaviours (smoking, alcohol use, fruit and vegetable intake, and moderate physical activity), mental health (depression and anxiety), and self-reported physical functioning and independent living.…”
Section: Introductionmentioning
confidence: 99%